Laparoscopic insertion of a pelvic tissue expander to prevent radiation enteritis prior to radiotherapy for sacral metastasis of alveolar maxillary rhabdomyosarcoma - Omejc, Andrej (Surgery and surgical endoscopy, 2019)
In patients receiving external beam radiotherapy to the pelvis, radiation enteritis is a significant complication, particularly in patients receiving high-dose radiotherapy (> 80 Gy) and in those with a low pelvic peritoneal reflection, allowing loops of the small intestine to enter the radiation field. The lifelong morbidity of radiation enteritis has motivated attempts at a variety of surgical displacement procedures in the abdomen, pelvis, and retroperitoneum. Displacement of organs using omentum, tissue expanders, breast prostheses, and several types of mesh has been reported, but none of these methods have gained widespread usage. Morbidity related to the surgical procedure itself has raised some concerns. Laparoscopic insertion and subsequent removal of a pelvic tissue expander before and after external beam radiotherapy is a relatively convenient, safe, and effective method for displacing loops of intestine out of the pelvis. This can be done with minimal morbidity and convert previously untreatable patients into treatable patients who can receive relatively high doses of radiation. Here, we report a case of 15-year-old female with maxillary rhabdomyosarcoma involving the maxillary sinus with skeletal metastases who was scheduled for second-line treatment of metastases with radiotherapy. A tissue expander was laparoscopically inserted into the lower pelvis to displace intestinal loops from the radiation field to prevent radiation enteritis.
Keywords: abdominalna kirurgija; laparoskopija; obsevanje; radiacijski enteritis; rak (medicina)